2004
DOI: 10.1002/er.1016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steam addition on flame structure and NO formation in H2–O2–N2 diffusion flame

Abstract: SUMMARYNumerical analysis is conducted to clarify chemical effects of added steam to either fuel-or oxidizer-side on flame structure and NO emission behaviour with detailed chemistry in hydrogen-oxygen-nitrogen diffusion flames. An artificial species, which has the same thermodynamic, transport, and radiation properties to added H 2 O, is introduced to feasibly isolate chemical effects of added H 2 O. It is found that the reaction step (-R23) is the starting point to induce chemical effects of added steam. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The effects of adding various components of exhaust gas on the formation of pollutants have also been investigated by some researchers (Bundy et al, 2003;Guo and Smallwood, 2008;Li and Williams, 1999;Liu et al, 2001;Lock et al, 2007;Park et al, 2004;Zhao et al, 2002). Generally an additive to the oxidant or fuel stream of a diffusion flame causes variations in flame liftoff and other properties due to the change in combustion intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of adding various components of exhaust gas on the formation of pollutants have also been investigated by some researchers (Bundy et al, 2003;Guo and Smallwood, 2008;Li and Williams, 1999;Liu et al, 2001;Lock et al, 2007;Park et al, 2004;Zhao et al, 2002). Generally an additive to the oxidant or fuel stream of a diffusion flame causes variations in flame liftoff and other properties due to the change in combustion intensity.…”
Section: Introductionmentioning
confidence: 99%
“…According to the OH concentration profile across the reaction zone, it was observed that the H 2 O and N 2 vitiation gas had almost the same peak concentration, although the adiabatic flame temperature with H 2 O vitiation gas was lower. This can be explained by the results of the previous research work, which indicated that more OH radicals were produced based on the chemical reaction step O + H 2 O → OH + OH [8,9]. At high flame temperature, the steam dissociation could also contribute to OH production [10].…”
Section: Reaction Zone Characteristicsmentioning
confidence: 84%
“…The previous study compared the experimental data of Rørtveit et al with numerical results simulated with the aforementioned reaction mechanisms for the hydrogen flame diluted with 0.6 mole fraction of added N 2 . It was shown that the predicted temperature profile with the GRI v-3.0 mechanism had the best agreement with the experimental data.…”
Section: Numerical Strategiesmentioning
confidence: 99%